Drunken angel [videorecording (DVD)] - Kurosawa, Akira, 1910-1998; Shimura, Takashi, 1905-1982; Mifune, Toshiro, 1920-1997; Yamamoto, Reizaburo (Criterion collection (DVD videodiscs), 2007)
A criminal infected with tuberculosis in Tokyo forms a friendship with an alcoholic physician.